Epidemiological and Clinical Determinants of Cutaneous Leishmaniasis in District Dir Upper Khyber Pakhtunkhwa, Pakistan: A Case-Based Analysis of 336 Confirmed Infections - Ullah, Wasia; Nasir , Abdul; Ahmad, Sahibzada Imtiaz; Rafi Ullah; Izaz, Muhammad; Islam, Ziaul; Rabia (Indus Journal of Bioscience Research, 2025)
Cutaneous leishmaniasis (CL) is a major public health concern in areas where it is prevalent, including District Upper Dir of Khyber Pakhtunkhwa, Pakistan. In order to determine risk factors and transmission patterns, this study examined the epidemiological and clinical features of 336 laboratory-confirmed CL cases. Significant ethnic differences were found in the data, with native Pakistanis accounting for 42.62% of cases and Afghan refugees for 57.37% (p < 0.0001). Wari (22.95%), Larjam (19.67%), and Dir (18.08%) were found to be high-burden sub-divisions by geospatial analysis (p < 0.0001). There was a male preponderance (57.14% vs. 42.86%; p = 0.002), and the most afflicted age group was children ages 1–10 (32.78%, p < 0.0001). The best times for sandfly activity were July (36.06%) through September (19.67%), when seasonal maxima occurred. Clinically, the face was the most prevalent lesion location (29.50%), and dry lesions (59.01%) outweighed moist lesions (40.99%; p < 0.0001). Workers (24.59%; p < 0.0001) and shepherds (34.42%) had the highest occupational hazards. These results emphasize the need for focused interventions in high-risk groups and seasonal transmission hotspots, highlighting the intricate interactions between behavioral, environmental, and demographic aspects in CL transmission. For the purpose of directing public health initiatives for CL control in endemic areas, this study offers vital evidence.